Priming the Secure Attachment Schema Affects the Emotional Face Processing Bias in Attachment Anxiety: An fMRI Research - Tang, Qingting; Chen, Xu; Hu, Jia; Liu, Ying (Frontiers in Psychology, 2017)
Our study explored how priming with a secure base schema affects the processing of emotional facial stimuli in individuals with attachment anxiety. We enrolled 42 undergraduate students between 18 and 27 years of age, and divided them into two groups: attachment anxiety and attachment secure.All participants were primed under two conditions, the secure priming using references to the partner, and neutral priming using neutral references. We performed repeated attachment security priming combined with a dual-task paradigm and functional magnetic resonance imaging. Participants’reaction times in terms of responding to the facial stimuli were also measured.Attachment security priming can facilitate an individual's processing of positive emotional faces; for instance, the presentation of the partner’s name was associated with stronger activities in a wide range of brain regions and faster reaction times for positive facial expressions in the subjects. The current finding of higher activity in the left-hemisphere regions for secure priming rather than neutral priming is consistent with the prediction that attachment security priming triggers the spread of the activation of a positive emotional state. However, the difference in brain activity during processing of both, positive and negative emotional facial stimuli between the two priming conditions appeared in the attachment anxiety group alone. This study indicates that the effect of attachment secure priming on the processing of emotional facial stimuli could be mediated by chronic attachment anxiety. In addition, it highlights the association between higher-order processes of the attachment system (secure attachment schema priming) and early-stage information processing system (attention), given the increased attention towards the effects of secure base schema on the processing of emotion- and attachment-related information among the insecure population. Thus, the following study has applications in providing directions for clinical treatment of mood disorders in attachment anxiety.